2018
DOI: 10.1016/j.neo.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

ETV7-Mediated DNAJC15 Repression Leads to Doxorubicin Resistance in Breast Cancer Cells

Abstract: Breast cancer treatment often includes Doxorubicin as adjuvant as well as neoadjuvant chemotherapy. Despite its cytotoxicity, cells can develop drug resistance to Doxorubicin. Uncovering pathways and mechanisms involved in drug resistance is an urgent and critical aim for breast cancer research oriented to improve treatment efficacy. Here we show that Doxorubicin and other chemotherapeutic drugs induce the expression of ETV7, a transcriptional repressor member of ETS family of transcription factors. The ETV7 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…Cells were harvested 16 hours after the administration of the drugs. In previous experiments, we had shown similar results with both a 10-hour and a 16-hour treatment schedule 2,28 .…”
Section: Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…Cells were harvested 16 hours after the administration of the drugs. In previous experiments, we had shown similar results with both a 10-hour and a 16-hour treatment schedule 2,28 .…”
Section: Methodssupporting
confidence: 79%
“…Previous studies showed the effect of E2 on p53 cellular localization and cell sensitivity to TNFα 1,11,27 . Treatment of MCF-7 with E2 decreases the transcription factor activity of p53 by transporting it to the cytoplasm, and subsequently, decreases the sensitivity to TNFα induced tumor suppressor effects 28 . In conclusion, these findings suggest that the combination treatment of Doxorubicin, E2 and TNFα may be involved in decreasing the expression and activity of ESR1 , potentially enhancing the chemotherapy efficacy in ER positive breast cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.5 × 10 6 HuH-7 cells were seeded in 150 mm dishes and allowed to adhere overnight, followed by 24 h treatment with 28 µM SLMP53-2 or DMSO. ChIP protocol was performed as described [51]. p53 occupancy at the p21 promoter was measured by RT-qPCR (primers are listed in Table S6).…”
Section: Methodsmentioning
confidence: 99%
“…ETV7 is a transcription factor belonging to ETS family, which has been proved to be responsible for the development of different tissues as well as the progression of several cancers, such as HCC (24,25). Due to its translocation function, the overexpression of ETV7 has been associated with tumorigenic transformation and anti-apoptosis by blocking Mys-induced apoptosis pathway (26)(27)(28). Furthermore, there are growing experimental evidences showing that ETV7 also plays a significant role in mTOR signaling pathway by assembling mTOR3 complex, which can stimulate cell proliferation and is not sensitive to rapamycin, a common anti-tumor agent, unlike mTOR1/2 (29).…”
Section: Precise Stratification Of Tcga-lihc Samples Based On Metabolmentioning
confidence: 99%